2014
DOI: 10.3748/wjg.v20.i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of circulating hepatocellular carcinoma cells to prevent postoperative recurrence and metastasis

Abstract: Currently, the main treatment for hepatocellular carcinoma (HCC) involves the surgical removal of tumors or liver transplantation. However, these treatments are often not completely curative, as they are associated with a risk for postoperative recurrence and metastasis. Circulating tumor cells (CTCs) are increasingly recognized as the main source for recurrence and metastasis after radical hepatectomies are performed. Many studies have demonstrated the association between the presence of either pre- or postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Norris et al showed that hepatocytes could directly synthesize IL6 mRNAs and protein following hepatic stimuli, including partial hepatectomy [40]. Circulating tumor cells can lead to recurrence and metastasis of HCC after liver transplantation [41]. We speculate that donor hepatocytes alter not only local IL6 levels in the liver but also serum IL6 levels, both of which promote recurrence and metastasis after transplantation by acting on the circulating tumor cells.…”
Section: Discussionmentioning
confidence: 94%
“…Norris et al showed that hepatocytes could directly synthesize IL6 mRNAs and protein following hepatic stimuli, including partial hepatectomy [40]. Circulating tumor cells can lead to recurrence and metastasis of HCC after liver transplantation [41]. We speculate that donor hepatocytes alter not only local IL6 levels in the liver but also serum IL6 levels, both of which promote recurrence and metastasis after transplantation by acting on the circulating tumor cells.…”
Section: Discussionmentioning
confidence: 94%
“…Circulating biomarkers such as serum AFP, VEGF, HGF, and TGF-β are still preferred for prognostic prediction. Circulating tumor cells (CTCs) may reflect tumor aggressiveness and serve as a promising candidate for predicting relapse and metastasis [58]. However, their utility is limited by the rarity of CTCs in the peripheral blood even if recent technical findings have made it possible to detect CTCs in multiple tumor types, including breast cancer [59], lung cancer [60] and others [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…As only patients with early-stage HCC are able to achieve optimal survival by radical hepatectomy or liver transplantation, the majority of patients are beyond curative intervention upon HCC diagnosis (1,2). Notably, existing alternative strategies, including chemotherapy and immunotherapy, have seldom elicited satisfactory responses in HCC (2,3).…”
Section: Introductionmentioning
confidence: 99%